Rating of the Social Institutions: Pupils‘ Opinion - Stulpinas, Tomas (Acta Paedagogica Vilnensia, 1999)
Social institutions according to the attitude of all the pupils are named in the following order: family, friends, teachers, classmates, church, media. The opinions of the respondents demonstrate the most general tendency. Pupils' opinions are very differentiated.
Keywords: rating of social institutions; family; friends; teachers; classmates; church; media